A multidimensional assessment of adverse events associated with paliperidone palmitate: a real-world pharmacovigilance study using the FAERS and JADER databases - Siyu Lou; Zhiwei Cui; Yingyong Ou; Junyou Chen; Linmei Zhou; Ruizhen Zhao; Chengyu Zhu; Li Wang; Zhu Wu; Fan Zou (BMC Psychiatry, 2025)
Abstract Objective Paliperidone palmitate is a second-generation antipsychotic that has undergone extensive investigation in clinical trials. However, real-world studies assessing its safety in large populations are lacking. As such, this study aimed to comprehensively evaluate real-world adverse drug events (ADEs) linked to paliperidone palmitate by employing data mining techniques on the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) database and the Japanese Adverse Drug Event Report (JADER) database. Methods The study retrieved ADE reports from the FAERS database covering the period from 2009 through the third quarter of 2024, and from the JADER database covering the period from 2013 through the second quarter of 2024. Utilizing disproportionality analyses such as the reporting odds ratios (ROR), proportional reporting ratios (PRR), Bayesian confidence propagation neural network (BCPNN), and multi-item Poisson shrinkage (MGPS), significant associations between ADEs and paliperidone palmitate were evaluated. Results A total of 27,672 ADE reports related to paliperidone palmitate were identified in FAERS, with 285 significantly disproportionate preferred terms (PTs) identified by all four algorithms. Paliperidone palmitate-associated ADEs encompassed 27 System Organ Classes (SOCs). The top three PTs with the highest reported cases were off-label use, drug ineffective, and hospitalization. Common ADEs included increased blood prolactin, galactorrhea, and schizophrenia, which was consistent with drug label. Noteworthy, unexpected signals not listed in the drug label were also identified, such as psychosexual disorders, prolactin-producing pituitary tumors, suicide attempt, and sudden death. The median onset time for all ADEs was 40 days. Furthermore, gender-based difference in risk signals was detected. Females are more likely to experience elevated blood prolactin and weight increase, whereas males are more prone to sexual dysfunction. Among the 1,065 ADE reports from the JADER database, we identified 51 positive signals, 35 of which overlapped with those found in FAERS, including schizophrenia, hyperprolactinemia, and erectile dysfunction. Conclusion The study findings from two independent databases serve as crucial references for ensuring the safe of paliperidone palmitate. Additionally, the gender-specific monitoring references provided can enhance clinical surveillance efforts and facilitate more effective risk identification.